Північне Причорномор'я у контактах цивілізацій - Біляєва, С.О. (Археологія і давня історія України, 2015)
У статті наданий порівняльний аналіз дії просторового фактору Північного Причорномор’я на
різних етапах взаємодії Русі-України з кочовими
спільнотами, цивілізаціями Золотої Орди, Османської та Російської імперій. У дискусійному
плані розглядаються концептуальні підходи до шляхів цивілізаційного розвитку. Геополитическое положение и специфика природных зон Северного Причерноморья обусловили
его значение в мировом историческом процессе как
район стыка локальных цивилизаций. В теоретико-методологическом плане проблематика стыка цивилизаций, конфликтов и противостояний сегодня
является чрезвычайно актуальной темой. В статье представлен сравнительный анализ специфики
взаимодействия Руси-Украины с кочевыми сообществами до-цивилизационного уровня (печенеги, торки, половцы), цивилизациями Золотой Орды и Османской империи, их борьбу за ключевые позиции на Черноморском побережье. В качестве предмета
дискуссий даны некоторые оценки концептуальных подходов С. Хантингтона о путях развития цивилизаций. Geopolitical location and the natural specific of the
North Black Sea area determinate it’s meaning in the
world historical process as the region of the junction
of the local civilizations. In the theoretical and methodological
sense the problems of the junction of the
civilizations, conflicts and understanding between one
another today is very actual. The article is devoted to
the comparative analyze of the specific of interaction of
the Rus-Ukraine with the medieval nomad’s societies, Golden Horde and the Ottoman civilization, its struggle
for the keynote positions on the Black Sea shore. As a subject for discussion some notes about conceptual
approaches of S. Huntington towards the ways of the development of the civilizations were represented.